Development of methods to increase the efficiency of road transportation by international transport corridors - Prokudin, Georgii; Chupaylenko, Alexey; Lebid, Viktoriia; Khobotnia, Tetiana (Technology audit and production reserves, 2020)
The object of research is the processes of managing the functioning of international transport corridors and projects for the transportation of goods, taking into account the assessment of the quality of transport services. There is a problem of assessing the quality of the international transport process taking into account such factors as the time of delivery of goods, the speed of movement of vehicles across the customs border and the tariff, which are determined by customer requirements. All these factors depend on the logistical support of transportation projects. The following methods were used to solve the tasks set in the work: the method of analysis of expert evaluations for the selection of project evaluation criteria; mathematical apparatus of decision theory; methods of simulation model for the assessment of the integral indicator of quality to achieve the optimal solution. Regularities of providing conditions of continuous, safe and convenient movement of traffic flows as a basis for creation of effective system of management of processes in a network of automobile international transport corridors are defined and the methodology of definition of efficiency of their functioning is developed. A method of forming a management system for the functioning and development of the network of international road transport corridors based on socio-economic forecasting in the form of a hierarchical structure of elements and their relationships has been developed. This made it possible to develop a model for forecasting the required amount of resources for road works on the basis of a certain demand from users of international road transport corridors. The study is aimed at obtaining new knowledge about the regularities of improving the efficiency of road transport along the routes of European international transport corridors, which can be used as a basis for the theory of determining its positive impact on the development of the economies of countries through which international transport corridors pass. In the course of the research, the approbation of the developed technique on a choice of the optimum project of transportation at the project-oriented enterprises of motor transport is carried out.